1999
DOI: 10.1037/0894-4105.13.4.590
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in episodic memory: The impact of verbal and visuospatial ability.

Abstract: The impact of verbal and visuospatial ability on sex differences in episodic memory was investigated. One hundred men and 100 women, 2040 years old, participated in a series of verbal and visuospatial tasks. Episodic memory was assessed in tasks that, to a greater or lesser extent, were verbal or visuospatial in nature. Results showed that women excelled in verbal production tasks and that men performed at a superior level on a mental rotation task. In addition, women tended to perform at a higher level than m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
93
5
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(119 citation statements)
references
References 44 publications
18
93
5
3
Order By: Relevance
“…1). Such results converge with previous findings that have shown better performance for females in episodic memory tasks (Herlitz et al, 1999;Herlitz & Yonker, 2002). Although this benefit was observed for both age groups, the benefit in memory performance for females over males was more consistently observed in the older adult sample.…”
Section: Itemsupporting
confidence: 69%
See 1 more Smart Citation
“…1). Such results converge with previous findings that have shown better performance for females in episodic memory tasks (Herlitz et al, 1999;Herlitz & Yonker, 2002). Although this benefit was observed for both age groups, the benefit in memory performance for females over males was more consistently observed in the older adult sample.…”
Section: Itemsupporting
confidence: 69%
“…Previous studies with young and older adults suggested a benefit for women in verbal episodic memory, as well as a comparable benefit for men in the visuospatial domain (see Herlitz, Airaksinen, & Nordstrom, 1999;Herlitz, Nilsson, & Backman, 1997;Herlitz & Rehnman, 2008;Lewin et al 2001). The memory benefit for verbal materials observed in women over men was confirmed in a study by Herlitz and Yonker (2002), who tested young adult men and women in a series of tasks involving the recall and recognition of verbal material, faces, and abstract pictorial stimuli.…”
Section: Gender Differences In Episodic Memorymentioning
confidence: 54%
“…Previous research has shown that there is a clear dissociation between episodic and semantic memory in relation to different variables, such as gender (e.g., Herlitz et al, 1997Herlitz et al, , 1999, age (e.g., Nilsson et al, 1997;Nyberg et al, 2003), genetic factors , and marital status (Mousavi-Nasab, Kormi-Nouri, Sundström, Nilsson, 2012). In general, 8 episodic memory has been found to be more affected by these variables than semantic memory.…”
Section: Introductionmentioning
confidence: 91%
“…After excluding this outlier, SPSS was used to conduct group (2) by sex (2) by retrieval task type (3) repeated-measures ANOVA to examine accuracy (significance threshold ϭ p Ͻ 0.05). Sex was included as a covariate in the analysis as previous studies have reported better spatial memory performance in men (Herlitz et al, 1999;Nyberg et al, 2000c;Lewin et al, 2001). Post hoc between-group one-way ANOVAs were conducted to clarify the 2-by-3 ANOVA results.…”
Section: Behavioral Analysismentioning
confidence: 99%